2014
DOI: 10.1111/cei.12301
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils from vasculitis patients exhibit an increased propensity for activation by anti-neutrophil cytoplasmic antibodies

Abstract: SummaryAnti-neutrophil cytoplasmic antibodies (ANCA) are thought to be pathogenic in ANCA-associated vasculitis (AAV) by stimulating polymorphonuclear leucocytes (PMNs) to degranulate and produce reactive oxygen species (ROS). The aim of this study was to investigate if PMNs from AAV patients are stimulated more readily by ANCA compared with PMNs from healthy controls (HCs). Differences in ANCA characteristics that can account for different stimulation potential were also studied. PMNs from five AAV patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 27 publications
(36 reference statements)
1
39
0
Order By: Relevance
“…Ohlsson et al . reported that neutrophils in patients with ANCA‐associated vasculitis exhibited an increased propensity for activation by cANCAs . Studies by Pankhurst et al .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ohlsson et al . reported that neutrophils in patients with ANCA‐associated vasculitis exhibited an increased propensity for activation by cANCAs . Studies by Pankhurst et al .…”
Section: Introductionmentioning
confidence: 98%
“…ANCA-mediated neutrophil activation seems to involve both Fc and Fab fragments of the antibody, but the exact mechanism of this process is not completely understood [2][3][4]. Ohlsson et al reported that neutrophils in patients with ANCA-associated vasculitis exhibited an increased propensity for activation by cANCAs [5]. Studies by Pankhurst et al showed that different immunoglobulin G subclasses of ANCA had different abilities for neutrophil activation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Immunoglobulin (Ig)G-class PR3-ANCA as well as MPO-ANCA can bind their target antigens exposed on the neutrophil surface (for instance, after cytokine-priming), resulting in cross-linking of Fc-receptors, complement activation and neutrophil oxidative burst [3,[11][12][13][14][15][16][17][18]. ANCA of different isotypes have been described previously, including IgG, IgA and IgM-ANCA, where IgG-ANCA is the predominating circulating isotype in AAV, and is monitored frequently in GPA as a means to assess disease activity [19][20][21], although the clinical utility remains controversial [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…NETs are lattice-like structures containing DNA, histones, and neutrophil granule proteins, including the ANCA antigens MPO and PR3 (12,17,18). ANCA-stimulated neutrophils were shown to release NETs in vitro, and circulating as well as glomerular deposited NETs were detected in AAV patients (12,(19)(20)(21). It was suggested that NETs are immunogenic and participate in the tolerance breakdown toward the ANCA autoantigens (12,22,23).…”
mentioning
confidence: 99%